2012
DOI: 10.1111/j.1365-2036.2012.05054.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose rabeprazole–amoxicillin dual therapy and rabeprazole triple therapy with amoxicillin and levofloxacin for 2 weeks as first and second line rescue therapies for Helicobacter pylori treatment failures

Abstract: SUMMARYBackground H. pylori eradication failures are difficult to treat and rescue therapies often consist of complex treatment regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
0
32
1
Order By: Relevance
“…24 Goh et al reported that the eradication rate of high-dose rabeprazole-amoxicillin dual therapy (amoxicillin 3000 mg, rabeprazole 60 mg for two weeks) was 71.4% as rescue therapy. 25 Attumi et al performed the eradication rate of high-dose dexlansoprazole and amoxicillin dual therapy (amoxicillin 2000 mg, dexlansoprazole 240 mg for two weeks) was 53.8%. 26 The eradication rates of our 10 day and 14 day rifabutin, amoxicillin and PPI regimens were clearly superior to previous high-dose PPI-amoxicillin, thus it is probable that rifabutin contributes an additive effect or synergistic effect in our rifabutin, amoxicillin and PPI regimens.…”
Section: Discussionmentioning
confidence: 99%
“…24 Goh et al reported that the eradication rate of high-dose rabeprazole-amoxicillin dual therapy (amoxicillin 3000 mg, rabeprazole 60 mg for two weeks) was 71.4% as rescue therapy. 25 Attumi et al performed the eradication rate of high-dose dexlansoprazole and amoxicillin dual therapy (amoxicillin 2000 mg, dexlansoprazole 240 mg for two weeks) was 53.8%. 26 The eradication rates of our 10 day and 14 day rifabutin, amoxicillin and PPI regimens were clearly superior to previous high-dose PPI-amoxicillin, thus it is probable that rifabutin contributes an additive effect or synergistic effect in our rifabutin, amoxicillin and PPI regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Other fluoroquinolones such as moxifloxacin may also be useful second-line agents. One study showed a second-line eradication rate of 95.0% using 14-day moxifloxacin-based therapy and 78.9% for a 7-day regimen [40]. Tetracycline despite its history of very low resistance levels, unfortunately was not shown to be effective with eradication rates of 46.6% when given as a second-line regime with PPI and amoxicillin [41].…”
Section: Rescue Therapiesmentioning
confidence: 99%
“…Due to the high metronidazole resistance rate in Malaysia [21], [22], metronidazole is not recommended. In cases where the therapy failed, two consecutive rescue regimens are used [23], [24]. The first line rescue regimen consists of rabeprazole 20 mg three times daily and amoxicillin 1 g three times daily for two weeks [23].…”
Section: Introductionmentioning
confidence: 99%
“…In cases where the therapy failed, two consecutive rescue regimens are used [23], [24]. The first line rescue regimen consists of rabeprazole 20 mg three times daily and amoxicillin 1 g three times daily for two weeks [23]. Rabeprazole is less susceptible to the influence of genetic polymorphisms for CYP2C19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation